2019
DOI: 10.1039/c9ra00281b
|View full text |Cite
|
Sign up to set email alerts
|

Blue-emitting acridine-tagged silver(i)-bis-N-heterocyclic carbene

Abstract: The synthesis and photophysical properties of blue-emitting acridine-tagged silver(i)-bis-N-heterocyclic carbene are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Thus, the contribution of different excitations to the overall emission must be considered as the excitation from HOMO/HOMO‐2 of acridine/ NHC−Au−Cl to only LUMO/LUMO+2 of acridine/acridine−NHC−Au−Cl moiety. The similar emission trend was reported with 4,5‐bis[(N‐aryl‐imidazol‐2‐ylidene)methyl]acridine silver(I) hexafluoro‐phosphate [20] . The quantum shift of emission property from 1 to 2 to 3 can be attributed to the unique alkyl folding along with inter and intramolecular interactions.…”
Section: Resultssupporting
confidence: 78%
“…Thus, the contribution of different excitations to the overall emission must be considered as the excitation from HOMO/HOMO‐2 of acridine/ NHC−Au−Cl to only LUMO/LUMO+2 of acridine/acridine−NHC−Au−Cl moiety. The similar emission trend was reported with 4,5‐bis[(N‐aryl‐imidazol‐2‐ylidene)methyl]acridine silver(I) hexafluoro‐phosphate [20] . The quantum shift of emission property from 1 to 2 to 3 can be attributed to the unique alkyl folding along with inter and intramolecular interactions.…”
Section: Resultssupporting
confidence: 78%
“…5b, and obtained the low energy for the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) is 3.66 eV, which is consistent with the NHC ligand coordinated with other metal ion. [51][52][53] Combined with the optimized structural and the electronic cloud density, the Au-(His) 2 molecule exhibits a singlet ground-state electronic conguration with HOMO and the LOMO best described as a formally sp 2 -hydridized lone pair and an unoccupied p-orbital at the carbene carbon. The adjacent s-electron withdrawing and p-electrondonating nitrogen atoms stabilize this structure both inductively by donating electron density into the empty p-orbital.…”
Section: Dft Calculation Of Au-(his)mentioning
confidence: 99%
“…It was observed about 0.48 eV increase in the HOMO and LUMO energy gap in complex 56 . Researchers also found that the HOMO orbitals largely located on the NHC, whereas the LUMO predominately located on the acridine moiety, in complex 56 (Prabusankar et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Prabusankar et al synthesized, 4,5‐bis[(N‐isopropylimidazol‐2‐ylidene)methyl]acridine silver(I) hexafluorophosphate as complex 56 was and its photophysical properties were evaluated (Figure 18) (Prabusankar et al, 2019). The spectral and structural features of complex 56 was compared with theoretical studies.…”
Section: Methodsmentioning
confidence: 99%